2019
DOI: 10.1111/jfbc.12998
|View full text |Cite
|
Sign up to set email alerts
|

Jujube honey induces apoptosis in human hepatocellular carcinoma HepG2 cell via DNA damage, p53 expression, and caspase activation

Abstract: Jujube honey, a very popular honey in China, has been shown to own numerous biological properties. However, the anticancer effect and the underlying mechanisms of jujube honey in HepG2 cells have not been investigated to date. This study was designed to evaluate jujube honey‐induced apoptosis and its molecular mechanism in HepG2 and the following results were obtained. Firstly, treatment with jujube honey blocked cell cycle progression at the G0/G1 phase, reduced the mitochondrial membrane potential (Δψm), ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
(75 reference statements)
1
6
1
Order By: Relevance
“…47 Pinocambrin and chrysin, two important marker flavonoids found in honey, were detected in both honey varieties as tested by us here. 48 However, another important marker flavonoid i.e., pinobanksin, previously reported for some other honey samples/varieties were not detected in our study. This could be due to seasonal or geographical variation in the metabolite composition of honey.…”
Section: Food and Function Papercontrasting
confidence: 77%
See 1 more Smart Citation
“…47 Pinocambrin and chrysin, two important marker flavonoids found in honey, were detected in both honey varieties as tested by us here. 48 However, another important marker flavonoid i.e., pinobanksin, previously reported for some other honey samples/varieties were not detected in our study. This could be due to seasonal or geographical variation in the metabolite composition of honey.…”
Section: Food and Function Papercontrasting
confidence: 77%
“…68 Furthermore, another report by Cheng et al , 2019, elucidated the role of Jujube honey in inducing apoptosis in hepatocellular carcinoma cells (HepG2 cells) by the overexpression of p53 and activation of caspases. 48 Based on this evidence, in the current study the mode of cell death triggered by both MS and MF honeys in colon cancer cells was investigated. Data also showed an up-regulation of p53 and the involvement of caspases 3, 8 and 9 and this was in accordance with the mechanisms shown earlier for both Manuka and Tualang honey.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also found that STH from Sardinia induced a higher percentage of ROS in LoVo cells, which points to a better anticancer potential compared to manuka honey. Chinese jujube honey was reported to have a cytotoxic effect on HepG2 cells ( 30 ), and Chilean ulmo honey on Caco-2 cells ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Honey is one of the most complex foodstuffs found in nature and, indeed, the only sweetening agent that humans can use without processing [ 36 ]. Since ancient times, it has been regarded as a healthy food for its wide pharmacological activities, including antibacterial, antioxidant, anti-inflammatory, immunomodulation, and antitumor [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%